Work management under stress: a dynamic exploration of a motivation control theory of fatigue - Bobrova, Y; Papachristos, G (UK Chapter of the System Dynamics Society, 2019)
Psychological fatigue can develop when an individual is engaged in an activity and experiences stress. The development of fatigue results in individual health and performance decline, and the individual may feel demotivated or disengage completely from the activity. To investigate fatigue development and ways to cope with it, Hockey’s motivation control theory of fatigue is formalised and explored with a system dynamics model. The model reproduces the three work management modes proposed in the theory: engaged, disengaged and strain. These simulation results support the internal validity of the theory and build confidence in the model. Further simulation results extend the theory and reveal two additional, distinct behavioural patterns, that capture two more strain work management modes. The exploration of ways to cope with fatigue development reveals that it can be suppressed in all three strain work management modes, if an individual takes regular breaks. These can be regular small breaks, equivalent to weekend breaks, or a combination of small and large breaks, equivalent to weekend breaks and annual leave respectively. In all modes the reduction in fatigue development comes at a price of reduced overall performance. The results highlight an important trade-off between work pace, performance and fatigue. A constant pace of work ensures high performance and quick accomplishment of goals, but it is more likely to lead to stress and a subsequent feeling of fatigue. In contrast, a slower work pace and a combination of regular small and occasional big breaks reduces daily productivity but ensures that the feeling of fatigue is neutralised. The results highlight the importance of selfcontrol and self-motivation across the range of work management modes to establish healthy and productive work patterns.